ANALYSIS OF THE FINANCIAL EFFICIENCY OF COMMERCIAL BANKS AND THE FACTORS INFLUENCING IT - Otaxonov Shakhzod Umidjonovich (European Science Publishing, 2025)
This article presents an extended analysis of the financial efficiency of commercial banks and the key factors influencing it. The research focuses on evaluating key performance indicators such as profitability, liquidity, capital adequacy, and asset quality of commercial banks in Uzbekistan from 2019 to 2023. It also explores both internal and external determinants, including interest rate policies, technological transformation, regulatory environment, and macroeconomic conditions. Statistical tables and charts illustrate financial trends across several years. Finally, the paper offers practical recommendations for enhancing the financial sustainability, operational efficiency, and strategic resilience of the banking sector in Uzbekistan.
Keywords: Financial efficiency, commercial banks, profitability, liquidity, capital adequacy, asset quality, digital transformation, Uzbekistan.